Bandung Government Digital Strategy for Land and Building Tax Payment Systems - Irawan, Ariq Naufal; Setiawan, Tomi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
Payment of land and building taxes online is a implementation of digital transformation in tax payment services that are used by the community to improve public services. The problem in this research is that the implementation of digital transformation of land and building tax payments in the city of Bandung has not been maximized. The study aims to understand the digital strategy on the payment of land and building taxes in the city of Bandung. This study uses the theory of digital strategy by Scupola and Mergel to analysis and describe a digital strategy for paying land and building taxes online. Methods The research uses qualitative methods, with literature study, observation, and interviews. This type of research is descriptive.The location of the research at the Agency Management Revenue Regional of Bandung City. Research uses secondary data and primary data. The result of the research show that digital strategies on land and building tax payments in Bandung is not optimal, because the digital strategy that implemented only use part of the process. The researcher recommends that the Bandung City Regional Revenue Management Agency to use co-planning process, in the digital strategy for land and building payments in the Bandung City.